Are there differences in the treatment strategies and outcomes between high-risk multiple myeloma patients and those with low-risk disease and without comorbities? (Hematology Meeting Reports, 2009)
It is well recognized that multiple myeloma (MM) is a B-cell malignancy with great variability in clinical outcome: Median survival times are approximately 3 years with standard-dose therapy and about 4 to 5 years with intensive treatment programs, but survival may range between only a few months and more than 10 years. Therefore, it has been a relevant issue to identify prognostic indicators for the estimation of the individual patient’s outcome. Development of strategies to optimize treatment, particularly with the aim of risk-adapted therapies, has gained substantial importance due to the availability of novel agents for MM therapy.